Shape-stabilized phase change composites enabled by lightweight and bio-inspired interconnecting carbon aerogels for efficient energy storage and photo-thermal conversion. Issue 25 (20th June 2022) - Sun, Zongxu; Zhang, Huanzhi; Zhang, Qingfeng; Jing, Rui; Wu, Bojing; Xu, Fen; Sun, Lixian; Xia, Yongpeng; Rosei, Federico; Peng, Hongliang; Lin, Xiangcheng
Abstract : CA-FSPCMs were constructed using a lightweight and high strength carbon aerogel to encapsulate PEG-6000, fabricated using biomass xanthan gum and polyimide. Abstract : Carbon aerogels have been widely studied due to their high specific surface areas, strong adsorption capabilities and good thermal properties, which can be used to develop shape-stabilized phase change materials (PCMs). The porous framework of carbon aerogels plays a crucial role in enhancing the performance of composite PCMs. Here we report a lightweight and high strength three-dimensional (3D) carbon aerogel by using inexpensive biomass xanthan gum (XG) to eliminate the structural collapse and shrinkage observed in traditional polyimide (PI) carbon aerogels. The high stability of XG allows uniform dispersion of TiO2 nanoparticles in the framework, endowing the carbon aerogel with high light–thermal transfer performance. PEG 6000 was encapsulated using the high strength PI/XG/TiO2 carbon aerogel via vacuum impregnation, creating multi-functional carbon aerogel-based form-stable PCMs (CA-FSPCMs) with excellent thermal performance. The CA-FSPCMs demonstrated latent heat values up to 160.38 J g −1, with excellent thermal reliability even after 100 thermal cycles. Furthermore, their light–thermal conversion and storage efficiency exceeded 94.23%, and their thermal conductivity improved up to 0.82 W m −1 K −1 thanks to the PI/XG/TiO2 carbon aerogel. We also evaluated the morphology, anti-leakage performance, mechanical properties and thermal response properties of the CA-FSPCMs. The heat energy storage and release capabilities of the fabricated CA-FSPCMs are very promising for applications in temperature regulation.